Handbook on Communicating and Disseminating Behavioral Science. - Welch-Ross, Dr. Melissa K. K. (SAGE Publications, 2007)
The Handbook on Communicating and Disseminating Behavioral Science assembles for the first time in a single volume research, scholarship and practices from across relevant disciplines and professions to give a coherent picture for both students in the classroom and scholars. Designed as both a text and a handbook, it provides insights into the main actors, contemporary themes and approaches, key challenges, and the broader conditions that influence whether and how the work occurs. Contributors include: behavioral scientists; journalism and communication scholars; mass media reporters, editors.